Disiplin, Komitmen, Motivasi, Dan Pengaruhnya Terhadap Kinerja Pegawai Di CV Kalihmekar Semarang - Febriana, Artha; Novitasari, Hanindiar (Jurnal Manajemen dan Dinamika Bisnis (JMDB), 2024)
Human resources (HR) in private companies and government agencies are the main key in achieving the company goals, so that there is no vacancy in the position that will result in disrupting the company operations. The purpose of this study is to determine the influence of work discipline, commitment, and motivation on employee performance in CV. Kalihmekar Semarang. The population in this study is the workers of CV. Kalihmekar Semarang. The sampling technique used in this study is by census, which is taken from the entire working population of 60 people. The analysis technique used in this study is multiple regression analysis using SPSS 25. The results of this study show that work discipline, commitment, and motivation have a positive and significant effect on employee performance. Work discipline, commitment, and motivation simultaneously affect the employee performance.